EFEKTIVITAS PEMBELAJARAN DARING PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS XII MADRASAH ALIYAH NEGERI 1 PONTIANAK - Melliana, Sara; Lasmono, Djon; Martono, Martono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Melliana, Sara. 2021. "Effectiveness of Online Learning in Indonesian Language Subjects Class XII Madrasah Aliyah Negeri 1 Pontianak". Thesis of the Department of Language and Arts Education. Faculty of Teacher Training and Education, Tanjungpura University. The first advisor Prof. Dr. H. Martono, M.Pd. and Second Advisor Drs. Djon Lasmono, M.Pd study aims to determine the effectiveness of e−leraning learning the Covid−19 pandemic in Indonesian. The research was carried out on class XII IPS 3 students in the odd semester of the 2020/2021 school year. The research site is in Madrasah Aliyah Negeri 1 Pontianak. The formulation of the problem studied in this study is how to change face−to−face learning to distance learning using online media for class XII IPS 3 students at Madrasah Aliyah Negeri 1 Pontianak odd semester the 2020/2021 school year. The method used in this research is descriptive qualitative. Data collection techniques in this study used several methods, such as observation, interviews, documentation, and triangulation. The aspects assessed in this study are effectiveness of learning, the learning process, and the advantages and disadvantages of online learning. This research focuses on online learning in Indonesian subjects, online learning process in Indonesian subjects, and advantages and disadvantages in the implementation of online learning on Indonesian subjects during the covid-19 pandemic in class XII Social 3 at Madrasah Aliyah Negeri 1 Pontianak.